= a2 + 2a (b + c) + (b + c)2
= a2 + 2ab + 2ac + (b2 + c2 + 2bc)
= a2 + b2 + c2 + 2ab + 2bc + 2ca
Therefore, (a + b + c)2 = a2 + b2 + c2 + 2ab + 2bc + 2ca
● (a + b - c)2 = [a + b + (-c)]2
= a2 + b2 + (-c)2 + 2ab + 2 (b) (-c) + 2 (-c) (a)
= a2 + b2 + c2 + 2ab – 2bc - 2ca
Therefore, (a + b - c)2 = a2 + b2 + c2 + 2ab – 2bc - 2ca
● (a - b + c)2 = [a + (- b) + c]2
= a2 + (-b2) + c2 + 2 (a) (-b) + 2 (-b) (-c) + 2 (c) (a)
= a2 + b2 + c2 – 2ab – 2bc + 2ca
Therefore, (a - b + c)2 = a2 + b2 + c2 – 2ab – 2bc + 2ca
● (a - b - c)2 = [a + (-b) + (-c)]2
= a2 + (-b2) + (-c2) + 2 (a) (-b) + 2 (-b) (-c) + 2 (-c) (a)
= a2 + b2 + c2 – 2ab + 2bc – 2ca
Therefore, (a - b - c)2 = a2 + b2 + c2 – 2ab + 2bc – 2ca
http://www.math-only-math.com/square-of-a-trinomial.html